The effect of increasing toroidal magnetic field in the Globus-M spherical tokamak. (24th October 2018) - Bakharev, N.N.; Bulanin, V.V.; Chernyshev, F.V.; Gusev, V.K.; Khromov, N.A.; Kiselev, E.O.; Kurskiev, G.S.; Melnik, A.D.; Minaev, V.B.; Mironov, M.I.; Miroshnikov, I.V.; Patrov, M.I.; et al.
Abstract: In the final Globus-M experimental campaign B tor and I p were raised by 25% up to 0.5 T and 250 kA, respectively, expanding available range of experimental parameters. In these experiments an overall improvement in plasma performance was observed, plasma total stored energy and neutron rate increased significantly. The energy confinement time dependence on B tor and n e was close to linear. L-H transition threshold was 5–10 times higher than threshold predicted by the scaling. Despite the small plasma-wall distance, the level of radiation losses in the main plasma volume was relatively small and decreased as B tor rised. An increase in B tor and I p led to a decrease in the sawtooth-induced losses. While a rise in the plasma current led to a decrease of fast ion losses per TAE burst at the same amplitude; frequency of bursts and their amplitude increased. Doppler backscattering, applied to study TAE localization for the first time, revealed that TAE fluctuations are localized in the region of normalized minor radii ρ   =  0.5–0.75. A new movable 9-pin head probe provided data, necessary for power decay length scaling investigation. Significant power decay length contraction, stronger than predicted by Eich's scaling, was observed.